(3GdJMcje aj GdYbhO GdEOGQjI (B:s (3OQGSI ebGQfI (B/s - (3QGVj, QfG eMeOs ((3GdbGgQI (B:s (3GdeQcR Gdbhej ddEUOGQGJ GdbGfhfjI,s, 2016)
(3jJfGhd cJGH (B((3GdJMcje aj GdYbhO GdEOGQjI (B: (3OQGSI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3QfG eMeO QGVj(B) (3aj MhGdj (B(150) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdJMcje hGdYbhO GdEOGQjI aj GdbGfhf GdEOGQj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdJegjOj (B: (3GdJYQja HGdYbO GdEOGQj, GdaUd GdChd (B: (3JYQja GdJMcje GdEOGQj, GdaUd GdKGfj (B: (3ehba GdOhd ef GdJMcje aj GdYbhO GdEOGQjI, GdaUd GdKGdK (B: (3GdbQGQ GdJMcjej, GdaUd GdQGHY (B: (3BKGQ GdJMcje, GdeUGOQ hGdeQGLY(B.s
(3GdJYQja HGdYbO GdEOGQj(B-(3GdeYjGQ GdeejR ddYbO GdEOGQj(B-(3GdJejjR GdbVGFj ddYbhO GdEOGQjI(B-(3JYQja GdJMcje GdEOGQj(B-(3GdWHjYI GdbGfhfjI ddJMcje(B-(3JejjR GdJMcje GdEOGQj Yf ZjQg ef GdCfXeI GdeTGHgI dg(B-(3ehba GdOhd ef GdJMcje aj GdYbhO GdEOGQjI(B-(3GdbQGQ GdJMcjej(B-(3cjajI EUOGQ GdbQGQ GdJMcjej(B-(3JUOjb GdbQGQ GdJMcjej hJfajPg(B-(3GdWYf aj GdbQGQ GdJMcjej(B-(3BKGQ GdJMcje(B-(3eOi GdJYGQV Hjf GdJMcje hGdYbO GdEOGQj(B-(3GdJMcje hEHWGd GdYbO GdEOGQj(B-(3GdJMcje hcjajI GdMaGX Ydi NUGFU GdYbO GdEOGQj(B-(3JWHjb GdbGfhf GdEOGQj Ydi efGRYGJ GdYbhO GdEOGQjI CeGe gjFI GdJMcje(B.s
(3HHdjhLQGajI (B: (3UaMI (B130-141.s
Keywords: (3GdJMcje (B((3bGfhf EOGQj(B)s -- (3GdYQGbs; (3GdYbhO GdEOGQjIs -- (3bhGfjf hJTQjYGJs -- (3GdYQGbs